2015
DOI: 10.1186/s11671-015-1157-z
|View full text |Cite
|
Sign up to set email alerts
|

Direct Probing of Dispersion Quality of ZrO2 Nanoparticles Coated by Polyelectrolyte at Different Concentrated Suspensions

Abstract: This study reports useful application of the electrokinetic sonic amplitude (ESA) technique in combination with rheometry and electron microscopy techniques for direct probing the stability of low and high-concentrated zirconia (ZrO2) nanosuspensions in the presence of an alkali-free anionic polyelectrolyte dispersant Dolapix CE64. A comparative study of the electrokinetic characteristics and the rheological behavior of concentrated ZrO2 nanosuspensions has been done. Good agreement was obtained from relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…It has been shown that by changing the Andersen coefficient, the size distribution of the porosities also changes [10]. On the other hand, in this work, if the porosities were perfectly aligned, the amount of penetration would probably be much greater.…”
Section: Porositymentioning
confidence: 54%
See 1 more Smart Citation
“…It has been shown that by changing the Andersen coefficient, the size distribution of the porosities also changes [10]. On the other hand, in this work, if the porosities were perfectly aligned, the amount of penetration would probably be much greater.…”
Section: Porositymentioning
confidence: 54%
“…Dolapix CE64 (an electrosteric dispersant, ammonium salt of a polycarboxylic acid) (Zschimmer and Schwarz), Dolapix CE64 (Zschimmer & Schwarz GmbH Co., Germany), were used in this study as a dispersing agent. It is an ammonium salt of a polycarboxylic acid, that acts through electrosteric stabilization [10]. Sodium tripolyphosphate (TPP) and citric acid were used as additives as well.…”
Section: Methodsmentioning
confidence: 99%
“…Low amounts of SV and high values of PD indicate a stable suspension. 29,30 N suspension has the highest SV (0.7 cm 3 /g) and the lowest PD (6.2%). In this suspension, particles have a high tendency to absorb each other and thereby create a flocculated and heterogeneous agglomerated sediment structure.…”
Section: Packing Density and Sediment Volumesmentioning
confidence: 99%
“…Of the different water-soluble anionic polyelectrolyte dispersants available (e.g., PAA, PMAA), a new type of commercially available electrosteric dispersant agent, Dolapix CE64 (Zschimmer & Schwartz GmbH Co., Germany) was found to be the most suitable choice on basis of physical and chemical properties as well as practical experiments reported by different authors [3,[42][43][44][45][46][47][48][49][50][51][52]. According to the manufacturer information and result reported by different authors, Dolapix CE64 contains aqueous solution (~ 70 mass%) and ammonium salt (~ 30 mass%) of poly-(methacrylic acid) (PMAA-NH 4) , with a pH of 9 [3,[43][44][45][46][47][48][49][50][51][52].It has a molecular weight of 660 g/mol with a density (20°C) of approximately 1.2 g/cm 3 [3,[43][44][45][46][47][48][49][50][51][52]. It can easily dissociate in water and produces negatively charged polyions and ammonium counter-ions that create stability based on electrosteric interactions [3,[43][44][45][46][47][48][49]…”
Section: Dispersant Characterizationmentioning
confidence: 99%
“…According to the manufacturer information and result reported by different authors, Dolapix CE64 contains aqueous solution (~ 70 mass%) and ammonium salt (~ 30 mass%) of poly-(methacrylic acid) (PMAA-NH 4) , with a pH of 9 [3,[43][44][45][46][47][48][49][50][51][52].It has a molecular weight of 660 g/mol with a density (20°C) of approximately 1.2 g/cm 3 [3,[43][44][45][46][47][48][49][50][51][52]. It can easily dissociate in water and produces negatively charged polyions and ammonium counter-ions that create stability based on electrosteric interactions [3,[43][44][45][46][47][48][49][50][51][52]. Therefore, in this study Dolapix CE64 was used for highly concentrated suspensions stabilization.Dispersant concentration and solids concentration are both calculated in percentage by weight (abbreviated mass%) on dry powder basis.…”
Section: Dispersant Characterizationmentioning
confidence: 99%